Manufacturing planning and control systems - Vollmann, Thomas E (Irwin/McGraw-Hill, 1997)
Updated to reflect the latest ideas and practices in planning and control systems, this text details recent advances in producing goods and services more efficiently. Concepts explored include integrating marketing and historical forecast information, and capacity management in process industries.